Gereja Misioner di Tengah Masyarakat Kalimantan Tengah Indonesia Yang Plural - Eva Inriani (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2021)
Christianity exists and flourishes in Indonesin Central Kalimantan as a plural society, with challenges of intolerance, social inequalities, economic inequities, injustices in law enforcement, natural destruction, humanitarian crises, moral degradation, and other issues. Under these real conditions, the church need for a contextual and transformative mission is a necessity. This article uses a qualitative approach. While the research writing technique used in literature review or literature study. The results showed that the misioner church in the context of a pluralistic Indonesian Central Kalimantan society is a church that involves itself in relevant services for it’s community, the church is present as a bearer of the Gospel according to the context of Indonesian society, and participates in maintaining religious harmony among the multi religious in Indonesia. The missionary church makes a real contribution to improving the quality of people's lives, and realizing services for people who are marginalized socially, economically and politically. Through the life and ministry of Jesus, the church can find the paradigm of a contextual and transformative church mission, so that the church can become a missionary church and answer the challenges of the times. Kekristenan hadir dan berkembang di tengah masyarakat Kalimantan Tengah Indonesia yang plural, dengan tantangan intoleransi dan adanya berbagai permasalahan sosial, ketidakadilan penegakan hukum, perusakan alam, degradasi moral, dan persoalan-persoalan lainnya. Dalam kondisi demikian, kebutuhan gereja akan misi gereja yang kontekstual dan tranformatif adalah sebuah keniscayaan. Artikel ini menggunakan pendekatan kualitatif. Sedangkan teknik penulisan penelitian yang digunakan adalah literature review atau studi pustaka. Hasil penelitian menunjukkan bahwa gereja yang misioner dalam konteks masyarakat Kalimantan Tengah Indonesia yang plural adalah gereja yang melibatkan diri dalam pelayanan yang relevan bagi masyarakatnya, gereja hadir sebagai pembawa kabar baik sesuai dengan konteks masyarakatnya, dan turut serta menjaga kerukunan umat beragama di Indonesia. Gereja misioner memberikan sumbangsih nyata bagi peningkatan kualitas kehidupan masyarakat, dan mewujudkan pelayanan bagi masyarakat yang termarginal secara sosial, ekonomi maupun politik. Melalui kehidupan dan pelayanan Yesus, gereja dapat menemukan paradigma misi gereja yang kontekstual dan tranformatif, sehingga gereja dapat menjadi gereja yang misioner dan mampu menjawab tantangan zaman.